2016
DOI: 10.1088/2053-1583/4/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological effects of graphene-based materials

Abstract: Graphene-based materials (GBMs) are currently under careful examination due to their potential impact on health and environment. Over the last few years, ecotoxicology has started to analyze all the potential issues related to GBMs and their possible consequences on living organisms. These topics are critically considered in this comprehensive review along with some considerations about future perspectives. RECEIVED

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 51 publications
0
47
0
Order By: Relevance
“…3,12,13 In fact, MoS 2 and other engineered nanomaterials (ENMs) are able to enter rivers or lakes and thus, evaluating the aquatic toxicity of these materials is essential.…”
Section: -8mentioning
confidence: 99%
“…3,12,13 In fact, MoS 2 and other engineered nanomaterials (ENMs) are able to enter rivers or lakes and thus, evaluating the aquatic toxicity of these materials is essential.…”
Section: -8mentioning
confidence: 99%
“…The fact that GO had an effect on the pollen performance of both species, although with a different intensity, agrees well with the literature reporting the toxic effects of GO on phylogenetically unrelated model organisms. 16 However, the mechanisms of toxicity are still unclear: some authors reported that GO can mechanically damage cells or tissues with its sharp edges 36 and reduce metabolic activity and viability when it is internalized into cells. 37,38 The great majority, though, agrees that GO causes oxidative stress inducing the formation of reactive oxygen species.…”
Section: Effect Of Go On Pollen Performances and Viabilitymentioning
confidence: 99%
“…[12][13][14][15] In general, however, there is agreement on the greater toxicity of graphene oxide (GO) with respect to other GBMs. 16 This is likely due to the high number of oxygen functional groups, such as hydroxyl, carboxyl and epoxy, spread over the graphene lattice which render GO more hydrophilic and reactive towards the surrounding environment. 17 Expectedly, the effects of GBMs on seed plants were always evaluated on the vegetative body at different developmental stages, from seed germination to the flowering adult plants.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of environmental depollution, carbon based materials, mainly graphene and graphene oxide materials, followed a few distinct routes of development, which can be categorized as follows: depollution of drinking and industrial water through adsorption or photodegradation [31][32][33][34][35][36], the analysis of toxic substances in aqueous media through use of novel sensor materials [37][38][39], better methods for sample preparation involving the use of graphene oxide based materials [40][41][42][43][44][45][46][47][48][49][50][51][52] and last but not least the assessment of environmental fate and toxicity of these type of materials [53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the fight for environmental depollution cannot be complete and is useless if in the struggle to remove a toxic component from the environment we add another one which has the potential ICEPR 138-2 to be more toxic that the one we are aiming to remove. In this case, proper studies must be carried out to ensure, or at least assess the potential of new materials to cause an unwanted environmental impact [53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%